Effect of unit size on thermal fatigue behavior of hot work steel repaired by a biomimetic laser remelting process. (1st January 2018) - Cong, Dalong; Li, Zhongsheng; He, Qingbing; Chen, Dajun; Chen, Hanbin; Yang, Jiuzhou; Zhang, Peng; Zhou, Hong
Highlights: Martensitic microstructure with ultrafine grain size was formed in units. Crack tip blunting and blocking increased the propagation resistance. Effects of unit size on thermal fatigue resistance were discussed. Abstract: AISI H13 hot work steel with fatigue cracks was repaired by a biomimetic laser remelting (BLR) process in the form of lattice units with different sizes. Detailed microstructural studies and microhardness tests were carried out on the units. Studies revealed a mixed microstructure containing martensite, retained austenite and carbide particles with ultrafine grain size in units. BLR samples with defect-free units exhibited superior thermal fatigue resistance due to microstructure strengthening, and mechanisms of crack tip blunting and blocking. In addition, effects of unit size on thermal fatigue resistance of BLR samples were discussed.